Implementation of a Participatory Tutoring Program to Improve Motivation and Academic Achievement of Elementary School Students in Mangkung Village, Central Lombok - Yuli Astuti; Adella Ulyandana Jayatri; Ika Umratul Asni Aminy; Rahmatun Inayah; Syamsuddin Syamsuddin; M. Arwenda Prayogi; Yusuf Idrus; Muhammad Kamiluddin; Indra Budiman; Kormil Saputra (Future Tecno-Science Publisher, 2026)
Basic education plays a crucial role in developing students' cognitive abilities and motivation to learn, yet students in rural areas still face limited resources and learning support. This community service initiative aims to improve the learning outcomes and motivation of elementary school students through a community-based tutoring program in Mangkung Village, Central Lombok Regency. The implementation method employed a participatory and collaborative approach with a one-month offline learning program involving 19 elementary school students. Evaluation was conducted through pre-tests and post-tests, as well as observations of learning behavior. The results showed an increase in students' average grades from 61.3 to 78.5, high attendance (90-100%), and positive changes in student engagement, discipline, and self-confidence. These results demonstrate that community-based tutoring is effective in improving students' cognitive and affective aspects.